2020
DOI: 10.1093/cid/ciaa347
|View full text |Cite
|
Sign up to set email alerts
|

A Community-transmitted Case of Severe Acute Respiratory Distress Syndrome (SARS) Due to SARS-CoV-2 in the United States

Abstract: This is the first known community transmission case of the novel coronavirus disease (COVID-19) in the United States, with significant public health implications. Diagnosis of COVID-19 is currently confirmed with PCR based testing of appropriate respiratory samples. Given the absence of travel or known exposure history, this patient did not meet the criteria for testing according to CDC guidelines at the time of her presentation. Since this case, any patient with severe disease (eg, ARDS or pneumonia) requirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Another report detailing the first case of community‐transmitted SARS‐CoV‐2 in the United States demonstrated similar complications of delayed diagnosis and treatment with remdesivir was recently published. Similar to our case, the authors observed clinical improvement after treatment with remdesivir initiated on day 11 of illness 16 …”
Section: Discussionsupporting
confidence: 89%
“…Another report detailing the first case of community‐transmitted SARS‐CoV‐2 in the United States demonstrated similar complications of delayed diagnosis and treatment with remdesivir was recently published. Similar to our case, the authors observed clinical improvement after treatment with remdesivir initiated on day 11 of illness 16 …”
Section: Discussionsupporting
confidence: 89%
“…Patient source control (e.g., patient wearing a mask or connected to a closed-system ventilator during HCP exposures) might also reduce risk of SARS-CoV-2 transmission. Although the index patient was not masked or ventilated for the majority of hospital A admission, at hospital B, where the patient remained on a closed system ventilator from arrival to receiving a positive test result, none of the 146 HCP identified as exposed developed known COVID-19 infection (8). Source control strategies, such as masking of patients, visitors, and HCP, should be considered by health care facilities to reduce risk of SARS-CoV-2 transmission.…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 virus (2019-nCoV/USA-CA9/2020) was isolated from the nasal swab of a COVID-19 patient with acute respiratory distress syndrome admitted to University of California, Davis Medical Center, Sacramento ( 48 ). Vero cells (ATCC CCL-81) were used for viral isolation and stock expansion.…”
Section: Methodsmentioning
confidence: 99%